The castle keepers - Runyan, Aimie K.; Ciesielski, J'nell; McMillan, Rachel, 1981- (Harper Muse, 2023)
"From three beloved authors comes a collection of stories that examines questions of healing, legacy, and love against the rich backdrop of a historical castle--and its adjoining poison garden"--